Competing logics and reform strategies in local reform: A case study of administrative licensing reform in China. Issue 4 (15th November 2022) - Yang, Zhenjie; Liang, Yuqing; Yu, Mengyan
Abstract: How to balance the market and the government to promote local economic development and provide sufficient public services has always been a challenging issue for leaders, in face of the existence of varied interests and values of different stakeholders. Conflicting values between the market and the government are directly related to the competing logics between market orientation and bureaucratic/administrative dominance. Since China's transition from the planned economy or government dominance to marketization in 1978, a series of national and local innovations has been launched. Among those reforms, policy entrepreneurs played a critical role. Administrative licensing reform was one of key changes from the planned economy to the marketized economy. Through a local case in administrative licensing reform, this study explores how a policy entrepreneur at local level applied reform strategies to balance conflicting values and constrain the self‐interested bureaucracy to achieve the marketization reform. 摘要: 鉴于存在不同的利益、价值观和利益攸关方，如何平衡市场和政府，以促进地方经济发展并为居民提供充足的公共服务，这一直是领导者面临的挑战。市场与政府之间的价值观冲突基于市场导向与官僚/行政主导之间的竞争性逻辑。自1978年以来，中国已从计划主导或政府主导转向市场化，并在该领域进行了一系列国家创新和地方创新。其中，政治企业家在这些改革中发挥了关键作用。行政许可改革是从计划经济转向市场经济的关键指标之一。本研究旨在通过一个地方行政许可改革案例，探究地方层面的政治企业家如何运用改革策略来平衡冲突的价值观、并约束自利的官僚制度以实现市场化改革。 Resumen: Cómo equilibrar el mercado y el gobierno para promover el desarrollo económico local y brindar suficientes servicios públicos para los residentes siempre ha sido un tema desafiante para los líderes, ya que existían diversos intereses, valores y partes interesadas. Los valores en conflicto entre el mercado y el gobierno se basaron en las lógicas que compiten entre la orientación del mercado y el dominio de la burocracia/administración. China ha avanzado en la transición de la planificación o el dominio del gobierno a la mercantilización desde 1978, con una serie de innovaciones nacionales y locales en esta área. Entre ellos, los empresarios políticos desempeñaron un papel fundamental en esas reformas. La reforma de las licencias administrativas fue uno de los indicadores clave de la economía de planificación a la economía de mercado. Este estudio tiene como objetivo explorar cómo un emprendedor político a nivel local aplicó estrategias de reforma para equilibrar los valores en conflicto y restringir la burocracia interesada en sí misma para lograr la reforma de la mercantilización a través de un caso local en la reforma de licencias administrativas.